Petroleum and Gas - Subsidence and Earth Movements Caused by Oil Extraction, or by Drilling Oil and Gas Wells (with Discussion) - W. T. Thom (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
Interest naturally attaches to fissuring and subsidence of the earth's surface, whatever the cause may be, and the induced movement and fissuring of the impervious strata overlying an oil sand is of even greater practical importance because of its bearing upon the recoverability of the portion of the oil not already extracted or extractable by ordinary production methods. It is probably true that significant ground movement induced by oil production occurs only in oil fields in relatively young formations, where the oil comes from incoherent or only slightly cemented sands and oil-soaked clays, but inasmuch as a great proportion of our "gusher" wells produce from "running" sands and yield a large part of the total oil output, it seems worth while to make an effort to inspire the collection and recording of data indicating the nature and magnitude of oil-field subsidence, both surface and subsurface. Goose Creek Field The single known instance in which the nature and magnitude of the surface subsidence incident to petroleum withdrawal has been accurately ascertained is that in the Goose Creek oil field of Texas, described by Pratt and Johnson.' There subsidence caused the submergence of a considerable area within the oil field, and, because the title to the naturally submerged lands of Texas rests in the State, it became necessary to determine whether the submergence was due to natural or artificial causes. A detailed study revealed that the sunken area conformed very closely to the limits of the productive oil field and that the cumulative depression over an eight-year period ranged from zero at the margin to 3.25 ft. at the center. This depression was accompanied by the development of local marginal surface fractures along which the subsiding ares